Family physicians' views on participating in prevention of major depression. The predictD-EVAL qualitative study. - Moreno-Peral, Patricia; Conejo-Cerón, Sonia; Fernández, Anna; Martín-Pérez, Carlos; Fernández-Alonso, Carmen; Rodríguez-Bayón, Antonina; Ballesta-Rodríguez, María Isabel; Aiarzagüena, José María; Montón-Franco, Carmen; King, Michael; Nazareth, Irwin; Bellón-Saameño, Juan Ángel (Public Library of Science, 2019)
Background The predictD intervention, a multicomponent intervention delivered by family physicians (FPs), reduced the incidence of major depression by 21% versus the control group and was cost-effective. A qualitative methodology was proposed to identify the mechanisms of action of these complex interventions. Purpose To seek the opinions of these FPs on the potential successful components of the predictD intervention for the primary prevention of depression in primary care and to identify areas for improvement. Method Qualitative study with FPs who delivered the predictD intervention at 35 urban primary care centres in seven Spanish cities. Face-to-face semi-structured interviews adopting a phenomenological approach. The data was triangulated by three investigators using thematic analysis and respondent validation was carried out. Results Sixty-seven FPs were interviewed and they indicated strategies used to perform the predictD intervention, including specific communication skills such as empathy and the activation of patient resources. They perceived barriers such as lack of time and facilitators such as prior acquaintance with patients. FPs recognized the positive consequences of the intervention for FPs, patients and the doctor-patient relationship. They also identified strategies for future versions and implementations of the predictD intervention. Conclusions The FPs who carried out the predictD intervention identified factors potentially associated with successful prevention using this program and others that could be improved. Their opinions about the predictD intervention will enable development of a more effective and acceptable version and its implementation in different primary health care settings.
Keywords: Depresión mental - Prevención; Depression; Primary Health Care; Prevention